User Acceptance of Computer Aided Audit Techniques and Tools by External Audit Professionals in Mongolia - Jargalsaikhan, Ariunaa (2013)
By virtue of the rapidly developing information technology solutions in accounting system, audit examination is urged to cope with such development to provide an opinion as to whether the accounting information expresses an accurate and impartial picture of the organization’s financial stand. Therefore, popularity of Computer Aided Audit Techniques and Tools (CAATTs) has been increased all over the world. The objective of this research is to examine user acceptance of CAATTs among Mongolian external audit professionals. Technology Acceptance Model 2 was utilized as theoretical foundation of the research. Organizational, social and individual factors were developed to test user acceptance via perceived usefulness, perceived ease of use and behavioral intention to use CAATTs. A total of 101 external auditors participated in as sample for the research. The data was collected via self-completion hand delivery questionnaire and analyzed through descriptive analysis, measurement and structural model assessment. The result of the research suggest that the auditors’ perception toward usefulness of CAATTs is positively affected by social and individual factors while rationalization toward easiness is positively influenced by organizational and social factors. Further, perception toward usefulness and easiness positively impact on external auditors’ intention to use CAATTs, however only perceived ease of use has significant relationship with actual usage of CAATTs.